Networking :social workers' response and involvement - Foo, Loke Min (University Malaysia Sarawak (UNIMAS), 1997)
Networking is a dynamic approach to deal with the increasingly complex issues of social problems of today. This study aims mainly to find out social workers' response and involvement in this relatively new approach, and also seek their suggestions on suitable models for networks.